An Overview of Biomaterials in Periodontology and Implant Dentistry. (9th January 2017) - Cho, Young-Dan; Seol, Yang-Jo; Lee, Yong-Moo; Rhyu, In-Chul; Ryoo, Hyun-Mo; Ku, Young
Abstract : Material is a crucial factor for the restoration of the tooth or periodontal structure in dentistry. Various biomaterials have been developed and clinically applied for improved periodontal tissue regeneration and osseointegration, especially in periodontology and dental implantology. Furthermore, the biomimetic approach has been the subject of active research in recent years. In this review, the most widely studied biomaterials (bone graft material, barrier membrane, and growth or differentiation factors) and biomimetic approaches to obtain optimal tissue regeneration by making the environment almost similar to that of the extracellular matrix are discussed and specifically highlighted.